Functional consequences of AXL sequence variants in hypogonadotropic hypogonadism - Salian-Mehta, S; Xu, M; Knox, A J; Plummer, L; Slavov, D; Taylor, M; Bevers, S; Hodges, R S; Crowley, Jr, W F; Wierman, M E (The journal of clinical endocrinology and metabolism, 2014)
Prior studies showed that Axl /Tyro3 null mice have delayed first estrus and abnormal cyclicity due to developmental defects in GnRH neuron migration and survival. The objective of the study was to test whether the absence of Axl would alter reproductive function in mice and that mutations in AXL are present in patients with Kallmann syndrome (KS) or normosmic idiopathic hypogonadotropic hypogonadism (nIHH). The sexual maturation of Axl null mice was examined. The coding region of AXL was sequenced in 104 unrelated, carefully phenotyped KS or nIHH subjects. Frequency of mutations was compared with other causes of GnRH deficiency. Functional assays were performed on the detected mutations. Axl null mice demonstrated delay in first estrus and the interval between vaginal opening and first estrus. Three missense AXL mutations (p.L50F, p.S202C, and p.Q361P) and one intronic variant 6 bp upstream from the start of exon 5 (c.586-6 C>T) were identified in two KS and 2 two nIHH subjects. Comparison of the frequencies of AXL mutations with other putative causes of idiopathic hypogonadotropic hypogonadism confirmed they are rare variants. Testing of the c.586-6 C>T mutation revealed no abnormal splicing. Surface plasmon resonance analysis of the p.L50F, p.S202C, and p.Q361P mutations showed no altered Gas6 ligand binding. In contrast, GT1-7 GnRH neuronal cells expressing p.S202C or p.Q361P demonstrated defective ligand dependent receptor processing and importantly aberrant neuronal migration. In addition, the p.Q361P showed defective ligand independent chemotaxis. Functional consequences of AXL sequence variants in patients with idiopathic hypogonadotropic hypogonadism support the importance of AXL and the Tyro3, Axl, Mer (TAM) family in reproductive development.